Four Tibetan lineages: core teachings of Pacification, Severance, Shangpa Kagyü, and Bodong - Blo-gros-mthav-yas (The library of Tibetan classics, 2021)
"Drawing primarily from the Pacification, Severance, Shangpa Kagyü, and Bodongpa traditions, Four Tibetan Lineages presents some of Tibet's most transformative yet lesser-known teachings on meditative practice. Most works in this volume are drawn from a Tibetan anthology known as the Treasury of Precious Instructions compiled by Jamgön Kongtrul Lodrö Thayé (1813-1900). A vast preservation project, this anthology reflects Kongtrul's attempt to rescue rare teachings from disappearing. By foregrounding the teachings of masters like Khedrup Khyungpo Naljor (d. 1135), Dampa Sangyé (d. 1117), Machik Labdrön (1031/55-1126/50), Jonang Taranatha (1575-1634), and Jamyang Khyentse Wangpo (1820-92), this volume extends Jamgön Kongtrul's preservation efforts into the modern world, presenting a set of rare teachings to English readers for the first time"--